STRUKTUR MIKRO BAHAN PROPELLER DARI KOMPOSIT ALUMINIUM 6061-ALUMINIUM OXIDE DENGAN METODE SQUEEZE CASTING - Santoso, Edi; Faizin Aswanto, Muhammad; Rigi Santoso, Achmad (Program Studi Teknik Mesin, Universitas 17 Agustus 1945 Surabaya, 2016)
The composite is a combination of two or more materials that form a bond, in which eachmaterial has different elements and forms a new material. One way to improve themechanical properties of composite materials is by heat treatment T6 consisting of threestages: 1. Solution treatment, 2. Quenching, 3. Artificial aging. The purpose of this study isas a comparison between the influence of type variations and temperature of cooling mediato the change of shape, dimensions, distribution of hardness and microstructure after andbefore T6 process of composite material aluminum 6061-aluminum oxide by squeeze castingmethod. In the process of T6 is done solution heat treatment at temperature 530℃ for 2 hoursand aging at temperature 180 ℃ for 2 hours. Specimen 9 with variations of coolant mediatype (water, brine, and oil SAE 40) and variations of coolant media temperature (roomtemperature, 70℃, dan 110℃). From the result of measurement and testing conducted showthat, changes in shape and dimensions are irregular due to non-uniform cooling rates. Thevalue of hardness increases after the heat treatment process and the value of hardness thatexist in the variation of the type and temperature of irregular cooling media, because it isinfluenced by the internal condition of the material. XRD microstructure testing showed thatall specimens in the compound candidate (Al, MgO, Si, and O) had a percentage value andthe compound formed differently. But the MgO compound affects changes in shape anddimension, If the value of MgO percentage is low then the change of shape and dimensionhas the biggest difference value. While the MgO is high then the change of shape anddimension has the smallest difference value